Matrix metalloproteinase 10 is linked to the risk of progression to dementia of the Alzheimer’s type - Adami, Pamela V. Martino; Orellana, Adelina; García, Pablo; Kleineidam, Luca; Alarcón-Martín, Emilio; Montrreal, Laura; Aguilera, Nuria; Espinosa, Ana; Abdelnour, Carla; Rosende-Roca, Maitee; Pablo Tartari, Juan; Vargas, Liliana; et al. (Brain, 2022)
Alzheimer’s disease has a long asymptomatic phase that offers a substantial time window for intervention. Using this window of opportunity will require early diagnostic and prognostic biomarkers to detect Alzheimer’s disease pathology at predementia stages, thus allowing identification of patients who will most probably progress to dementia of the Alzheimer’s type and benefit from specific disease-modifying therapies. Consequently, we searched for CSF proteins associated with disease progression along with the clinical disease staging.We measured the levels of 184 proteins in CSF samples from 556 subjective cognitive decline and mild cognitive impairment patients from three independent memory clinic longitudinal studies (Spanish ACE, n = 410; German DCN, n = 93; German Mannheim, n = 53). We evaluated the association between protein levels and clinical stage, and the effect of protein levels on the progression from mild cognitive impairment to dementia of the Alzheimer’s type.Mild cognitive impairment subjects with increased CSF level of matrix metalloproteinase 10 (MMP-10) showed a higher probability of progressing to dementia of the Alzheimer’s type and a faster cognitive decline. CSF MMP-10 increased the prediction accuracy of CSF amyloid-β 42 (Aβ42), phospho-tau 181 (P-tau181) and total tau (T-tau) for conversion to dementia of the Alzheimer’s type. Including MMP-10 to the [A/T/(N)] scheme improved considerably the prognostic value in mild cognitive impairment patients with abnormal Aβ42, but normal P-tau181 and T-tau, and in mild cognitive impairment patients with abnormal Aβ42, P-tau181 and T-tau. MMP-10 was correlated with age in subjects with normal Aβ42, P-tau181 and T-tau levels.Our findings support the use of CSF MMP-10 as a prognostic marker for dementia of the Alzheimer’s type and its inclusion in the [A/T/(N)] scheme to incorporate pathologic aspects beyond amyloid and tau. CSF level of MMP-10 may reflect ageing and neuroinflammation.